Internal Structure of the Oceanic Lithosphere at a Melt‐Starved Ultraslow‐Spreading Mid‐Ocean Ridge: Insights From 2‐D Seismic Data. (31st January 2020) - Momoh, Ekeabino; Cannat, Mathilde; Leroy, Sylvie
Abstract: Extensive outcrops of serpentinized peridotite in melt‐starved spreading corridors of the ultraslow easternmost Southwest Indian Ridge are hypothesized to be due to slip on successive long‐offset normal faults that alternate polarity (flip‐flop detachment faults). We investigate the nature of the oceanic crust which forms under these conditions, using seismic reflection data acquired during the SISMOSMOOTH 2014 cruise. Using 3‐D binning, the seismic profiles were binned elastically, while three of the profiles shot closely were merged into one to take advantage of the larger air gun source volume. Using a poststack imaging sequence, we observe several types of reflectors at crustal and infracrustal depths, in the axial valley and off‐axis. Correlating our seismic observations with Residual Mantle Bouguer gravity anomalies and seafloor observations, we find that our results are explicable in the framework of the flip‐flop hypothesis of detachment faulting. Reflectors imaged down to 5 km into the basement and interpreted as due to damaged zones outlining the detachment faults dip 50° at the early stages, while at late stages after developing offsets >10 km, they dip 25°. Other reflectors observed in the crust are interpreted as moderate offset (<200 m) normal faults accommodating deformation and alteration in the hanging wall and channeling the sparse melt to the seafloor. We interpret these and other observed seismic reflectors in the frame of a two‐phase evolutionary sequence over the lifetime of two successive flip‐flop detachment faults: exhumation, footwall flexure, damage, serpentinization, and incipient magmatism in the footwall of one detachment fault; followed by further tectonic damage, alteration, and incipient magmatism in the hanging wall of the next detachment fault. Key Points: Seismic reflectivity structure of amagmatic spreading corridor reveals signatures of possible flip‐flop detachment faults Detachment faults are steep‐dipping (>45°) in the upper 5 km of the ultramafic basement at the early stages and more shallow dipping (25°) after developing offsets >10 km Seismic reflectivity structure consistent with two‐phase accretion history: (1) tectonic exhumation in the footwall of a detachment fault, and (2) further faulting, alteration, and magmatic infiltration in the hanging wall of the next detachment fault